2020
DOI: 10.36892/ijlls.v2i3.317
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Factors Hindering Students’ Lesson Comprehension in EMI Classes

Abstract: The implementation of English as a medium of instruction (EMI) has been found to bring numerous benefits to its learners. There has been a rising trend in introducing EMI at higher education institutions worldwide. However, challenges are ubiquitous and there is still prevalent hesitation in integrating content and language in many institutions. This study aimed to explore factors hindering students’ level of lesson comprehension in EMI classes through a mixed-method study carried out on 233 participants at Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
1
Order By: Relevance
“…Phuong and Nguyen (2019) revealed that students recognized the benefits of EMI in terms of cognitive advantages, resource availability, opportunities to learn English due to more exposure, and increased employability. Tran et al (2020) discovered that the range of vocabulary, writing skills, and teaching methods used in EMI contributed significantly to students' predicted levels of comprehension. To date, EMI research in Vietnam has investigated the challenges that both teachers and students face, as well as some benefits that EMI courses can have for students (Tran and Nguyen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Phuong and Nguyen (2019) revealed that students recognized the benefits of EMI in terms of cognitive advantages, resource availability, opportunities to learn English due to more exposure, and increased employability. Tran et al (2020) discovered that the range of vocabulary, writing skills, and teaching methods used in EMI contributed significantly to students' predicted levels of comprehension. To date, EMI research in Vietnam has investigated the challenges that both teachers and students face, as well as some benefits that EMI courses can have for students (Tran and Nguyen, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tuy được rất nhiều kỳ vọng, nhiều nghiên cứu trên thế giới đã chỉ ra các môn học chuyên ngành thiết kế theo EMI bộc lộ nhiều hạn chế như khả năng tiếng Anh của sinh viên và giảng viên kém sẽ làm suy giảm đáng kể chất lượng đào tạo của môn học 1,2 . Tương tự tại Việt Nam, tuy các môn học chuyên ngành thiết kế theo EMI nằm trong định hướng chiến lược cần tăng cường trong các cơ sở giáo dục đại học 3 nhưng quy trình thực hiện vẫn bộc lộ nhiều hạn chế như khả năng truyền đạt bằng tiếng Anh của giảng viên 4 , khả năng tiếp thu và lĩnh hội tri thức của sinh viên 5…”
Section: Giới Thiệuunclassified